VERTEX-ECCENTRICITY DESCRIPTORS IN DENDRIMERS - AZARI, Mahdieh; IRANMANESH, Ali; DIUDEA, Mircea V. (Studia Universitatis Babeș-Bolyai Chemia, 2017)
In this paper, we present graph theoretical methods to compute several vertex-eccentricity-based molecular descriptors such as the eccentric connectivity index, total eccentricity, average eccentricity and first and second Zagreb eccentricity indices for the generalized and ordinary Bethe trees and some dendrimer graphs. Also, we study the behavior of these descriptors under the rooted product of graphs and apply our results to compute these indices for some classes of molecular graphs, designed by attaching copies of ordinary Bethe trees to paths and cycles.